Cytomorphological study of palpable Breast Lumps by FNAC - P. Venkataramana Babu; Neeraja M.; Varalakshmi K.P.; V. Sivasankara Naik; Sumankumar T.C.S.; Bhavani C.; Shravani P.; Sujeevaswapna R. (International Journal of Medical Research and Review, 2016)
Aim and Objective: To assess the distribution of various cytomorphological patters of clinically palpable breast lumps by Fine Needle Aspiration Cytology technique.Materials and Methods: A retrospective study over a period of 3 years 270 breast aspirates who attended the surgery out patient department in government medical college Anantapur from January 2012 to December 2014 were studied with clinical correlation and cytological analysis with FNAC. Smears were stained with H &E stain, and correlation with imaging studies, including mammography was done.Results and Analysis: Total of 270 cases were studied, out of these 191 (70.74%) were found benign and 50 (18.51%) were malignant. 20 (7.40%) cases given un- satisfactory results. Out of 270 cases of analysis, Fibroadenoma was the most common benign lesion found in 133 (49.25%) patients, followed by fibrocystic disease 28(10.37%) and mastitis/Breast abscess 8(2.96%) were common breast lesions on cytology. Malignant breast lesions constitute 50(18.51%) cases, among which Duct cell carcinoma 47(17.40%) cases were commonest type.Conclusion: Benign breast lesions are common than malignant lesions, fibroadenoma and fibrocystic disease are more common in benign disease. Maximum number of lesions (34%) was seen in age group of 20 to 30 years, whereas IDC accounts for the highest number of malignant lesions. Fine-needle aspiration cytology is a rapid and effective method for the primary categorization of palpable breast lumps into benign, malignant, atypical, suspicious, and unsatisfactory categories.